2020
DOI: 10.3389/fmicb.2020.01001
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive Regulation of Carbapenem Susceptibility in Pseudomonas aeruginosa by Hfq

Abstract: Carbapenems are often the antibiotics of choice to combat life threatening infections caused by the opportunistic human pathogen Pseudomonas aeruginosa. The outer membrane porins OprD and OpdP serve as entry ports for carbapenems. Here, we report that the RNA chaperone Hfq governs post-transcriptional regulation of the oprD and opdP genes in a distinctive manner. Hfq together with the recently described small regulatory RNAs (sRNAs) ErsA and Sr0161 is shown to mediate translational repression of oprD, whereas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 66 publications
3
26
0
Order By: Relevance
“…It acts as a pleiotro post-transcriptional regulator, which, in Pseudomonads, can act in concert with the cata lite repression control protein Crc [142,[146][147][148]. Hfq-dependent regulation controls tabolism [29] and virulence traits [47,51,124,[149][150][151], including the susceptibility to cl cally relevant antibiotics (Figure 3a) [52,75,152]. As mentioned above, Hfq can exert th functions by aiding riboregulation by sRNAs [47,51,52,153], but also by directly repress the translation of target mRNAs containing cognate Hfq-binding motifs [29,151].…”
Section: Translational Repressors and Their Rna Decoysmentioning
confidence: 98%
See 2 more Smart Citations
“…It acts as a pleiotro post-transcriptional regulator, which, in Pseudomonads, can act in concert with the cata lite repression control protein Crc [142,[146][147][148]. Hfq-dependent regulation controls tabolism [29] and virulence traits [47,51,124,[149][150][151], including the susceptibility to cl cally relevant antibiotics (Figure 3a) [52,75,152]. As mentioned above, Hfq can exert th functions by aiding riboregulation by sRNAs [47,51,52,153], but also by directly repress the translation of target mRNAs containing cognate Hfq-binding motifs [29,151].…”
Section: Translational Repressors and Their Rna Decoysmentioning
confidence: 98%
“…In addition, Sr0161 was suggested to regulate opdP mRNA, which encodes a second porin involved in carbapenem uptake [52]. However, recent studies revealed that opdP appears not to be regulated by sRNAs [75]. At variance, opdP appeared to be translationally repressed by a regulatory complex consisting of Hfq and the catabolite repression protein Crc (see below).…”
Section: Sr0161mentioning
confidence: 99%
See 1 more Smart Citation
“…ErsA is a well-characterized small RNA of P. aeruginosa, which has been proposed to serve a dual regulatory role in biofilm development, activating the mRNA of transcriptional regulator AmrZ while at the same time repressing the mRNA of AlgC, an important virulenceassociated enzyme for the production of sugar precursors (71,72). In addition, ErsA acts as a translational repressor of the mRNA of outer membrane porin OprD (73). ErsA is wellexpressed during the exponential growth phase (51) and bound by Hfq (8), making it an excellent candidate for validation by an independent technique of the infection-dependent changes seen in Grad-seq.…”
Section: Phage-induced Stress Affects Cellular Organization Of the Rnomementioning
confidence: 99%
“…Poor drug penetration is a major issue behind bacterial resistance to antibiotics. It can be attributable to reduced membrane permeability to antibiotics [ 14 ] and to the expression of efflux pumps which thwart the activity of antimicrobials by inducing their expulsion from the cell [ 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%